Hotspots of mite new species discovery: Sarcoptiformes (2013–2015) - Li, Guang-Yun; Zhang, Zhi-Qiang (Zootaxa, 2016)
A list of of type localities and depositories of new species of the mite order Sarciptiformes published in two journals (Zootaxa and Systematic & Applied Acarology) during 2013–2015 is presented in this paper, and trends and patterns of new species are summarised. The 242 new species are distributed unevenly among 50 families, with 62% of the total from the top 10 families. Geographically, these species are distributed unevenly among 39 countries. Most new species (72%) are from the top 10 countries, whereas 61% of the countries have only 1–3 new species each.  Four of the top 10 countries are from Asia (Vietnam, China, India and The Philippines).